2016
DOI: 10.1038/srep31368
|View full text |Cite
|
Sign up to set email alerts
|

Repeated superovulation may affect mitochondrial functions of cumulus cells in mice

Abstract: Controlled ovarian stimulation by exogenous gonadotrophins is a key procedure during the in vitro fertilization cycle to obtain a sufficient number of oocytes in humans. Previous studies demonstrated that repeated superovulation had deleterious effects on the ovaries. However, whether repeated superovulation adversely affects the mitochondrial functions of cumulus cells remains unclear. In this study, mice were divided into three groups: superovulation once (R1); superovulation three times (R3), and superovula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 36 publications
(43 reference statements)
3
17
0
Order By: Relevance
“…Besides, blastocyst and hatching rates decreased and elevated apoptosis was found in these blastocysts (Kalthur et al, ). In addition, messenger RNA expression of some genes such as Cox1 , Cytb , Nd2 , and Nd4 was altered in cumulus cells in response to repeated superovulation in mice (Xie et al, ).…”
Section: Embryonic Responses To Art‐induced Stress In the Mouse Modelmentioning
confidence: 99%
“…Besides, blastocyst and hatching rates decreased and elevated apoptosis was found in these blastocysts (Kalthur et al, ). In addition, messenger RNA expression of some genes such as Cox1 , Cytb , Nd2 , and Nd4 was altered in cumulus cells in response to repeated superovulation in mice (Xie et al, ).…”
Section: Embryonic Responses To Art‐induced Stress In the Mouse Modelmentioning
confidence: 99%
“…**p < 0.01, ***p < 0.001. 5mc: 5-methylcytosine [Color figure can be viewed at wileyonlinelibrary.com] Albertini, 2003; Kalthur et al, 2016;Xie et al, 2016). By using a murine model, we found that repeated superovulation reduces oocyte quality by disrupting meiotic cytoskeletal assemblies, mitochondrial function, and genomic DNA methylation; elevating oocyte apoptosis; and inducing oxidative stress.…”
Section: Discussionmentioning
confidence: 92%
“…The oxidative damage, including an increased content of 8-OH-dG, lipid peroxides and protein carbonyls, positively correlated with the number of COH cycles [ 51 ]; it induced mitochondrial abnormalities and a decrease in antioxidants compatible with ovarian aging [ 52 ]. The effects of COH were determined also in mouse cumulus cells, where the mtDNA copy number decreased as the number of stimulation increased, together with altered DNA methylation in nuclear-encoded DNA polymerase gamma A (PolgA] and consequent changes in PolgA expression [ 53 ]. Moreover, mRNA expression levels of cytochrome b (CYTB), cytochrome c oxidase subunit 1 (COX1), NADH dehydrogenase subunit (ND4), and NADH dehydrogenase subunit 2 (ND2), all encoded by mtDNA, were altered following repeated superovulation in cumulus cells [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of COH were determined also in mouse cumulus cells, where the mtDNA copy number decreased as the number of stimulation increased, together with altered DNA methylation in nuclear-encoded DNA polymerase gamma A (PolgA] and consequent changes in PolgA expression [ 53 ]. Moreover, mRNA expression levels of cytochrome b (CYTB), cytochrome c oxidase subunit 1 (COX1), NADH dehydrogenase subunit (ND4), and NADH dehydrogenase subunit 2 (ND2), all encoded by mtDNA, were altered following repeated superovulation in cumulus cells [ 53 ]. Detrimental effects of repeated cycles of COH on mitochondria were seen by the reduction of ATP production on GV-stage mouse oocytes matured in vitro after four rounds [ 54 ].…”
Section: Discussionmentioning
confidence: 99%